MODEL REFORMASI PENDIDIKAN EKONOMI MENUJU PENDIDIKAN BERKARAKTER - Caska ' (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
The aim of this research was to identify solving problem technique to improve the competence of students in Senior High School. Data were collected by using survey and descriptive research in 36 Senior High School in 12 regencies, Riau Province. The results of this study showed solving problem technique to improve students’ competence were: (1) Repairing in components; (2) Standard process. 3) The standard of educational management. (4) The standard of educational and educator. (5) The improvement of implementation component. Keywords: Educational Quality, educational reform, state exam.